Primordial origin and diversification of plasmids in Lyme disease agent bacteria - Casjens, Sherwood R.; Di, Lia; Akther, Saymon; Mongodin, Emmanuel F.; Luft, Benjamin J.; Schutzer, Steven E.; Fraser, Claire M.; Qiu, Wei-Gang (BMC genomics, 2018)
Background With approximately one-third of their genomes consisting of linear and circular plasmids, the Lyme disease agent cluster of species has the most complex genomes among known bacteria. We report here a comparative analysis of plasmids in eleven Borreliella (also known as Borrelia burgdorferi sensu lato) species. Results We sequenced the complete genomes of two B. afzelii, two B. garinii, and individual B. spielmanii , B. bissettiae, B. valaisiana and B. finlandensis isolates. These individual isolates carry between seven and sixteen plasmids, and together harbor 99 plasmids. We report here a comparative analysis of these plasmids, along with 70 additional Borreliella plasmids available in the public sequence databases. We identify only one new putative plasmid compatibility type (the 30th) among these 169 plasmid sequences, suggesting that all or nearly all such types have now been discovered. We find that the linear plasmids in the non- B. burgdorferi species have undergone the same kinds of apparently random, chaotic rearrangements mediated by non-homologous recombination that we previously discovered in B. burgdorferi . These rearrangements occurred independently in the different species lineages, and they, along with an expanded chromosomal phylogeny reported here, allow the identification of several whole plasmid transfer events among these species. Phylogenetic analyses of the plasmid partition genes show that a majority of the plasmid compatibility types arose early, most likely before separation of the Lyme agent Borreliella and relapsing fever Borrelia clades, and this, with occasional cross species plasmid transfers, has resulted in few if any species-specific or geographic region-specific Borreliella plasmid types. Conclusions The primordial origin and persistent maintenance of the Borreliella plasmid types support their functional indispensability as well as evolutionary roles in facilitating genome diversity. The improved resolution of Borreliella plasmid phylogeny based on conserved partition-gene clusters will lead to better determination of gene orthology which is essential for prediction of biological function, and it will provide a basis for inferring detailed evolutionary mechanisms of Borreliella genomic variability including homologous gene and plasmid exchanges as well as non-homologous rearrangements.